Characteristics of Transmissible CTX-M- and CMY-Type β-Lactamase-Producing Escherichia coli Isolates Collected from Pig and Chicken Farms in South Korea - Shin, Seung Won; Jung, Myunghwan; Won, Ho Geun; Belaynehe, Kuastros Mekonnen; Yoon, In Joong; Yoo, Han Sang (Journal of microbiology and biotechnology, 2017)
The rapid dissemination of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli has significantly contributed to public health hazard globally. A total of 281 strains recovered from pigs and chickens between 2009 and 2015 in South Korea were analyzed for ESBL production. ESBL phenotypes were recognized in 14 isolates; ten and three ESBLproducing isolates carried only and genes, respectively, and one isolate harbored both genes. The predominant CTX-M and CMY types were CTX-M-15 (n = 8) and CMY-2 (n = 3). We also detected ESBL-producing isolates harboring , , , , and genes. All ESBL-producing isolates showed resistance to the extent of the fourth generation cephalosporins, along with multidrug resistance. CTX-M-15- producing isolates showed higher MIC values than CTX-M-14- and CTX-M-65-producing isolates. The and genes have the potential to be transferable. The spreading of and genes was arbitrated mainly v ia F rep a nd I ncI1 plasmids. Our i solates showed clonal diversity in PFGE analysis. This is the first report of isolates carrying in chicken from South Korea. The emergence of CMY-6 ESBLs in a population of poultry suggests that extensive screening with long-term surveillance is necessary to prevent the dissemination of ESBL from chicken to human.